Egg eviction imposes a recoverable cost of virulence in chicks of a brood parasite. - Michael G Anderson (Public Library of Science (PLoS), 2009)
Background Chicks of virulent brood parasitic birds eliminate their nestmates and avoid costly competition for foster parental care. Yet, efforts to evict nest contents by the blind and naked common cuckoo Cuculus canorus hatchling are counterintuitive as both adult parasites and large older cuckoo chicks appear to be better suited to tossing the eggs and young of the foster parents. Methodology/principal findings Here we show experimentally that egg tossing imposed a recoverable growth cost of mass gain in common cuckoo chicks during the nestling period in nests of great reed warbler Acrocephalus arundinaceus hosts. Growth rates of skeletal traits and morphological variables involved in the solicitation of foster parental care remained similar between evictor and non-evictor chicks throughout development. We also detected no increase in predation rates for evicting nests, suggesting that egg tossing behavior by common cuckoo hatchlings does not increase the conspicuousness of nests. Conclusion The temporary growth cost of egg eviction by common cuckoo hatchlings is the result of constraints imposed by rejecter host adults and competitive nestmates on the timing and mechanism of parasite virulence.